Fetal marrow suppression after maternal chemotherapy for leukaemia. Issue 3 (November 1994) - Murray, N A; Acolet, D; Deane, M; Price, J; Roberts, I A
Abstract : A preterm baby, whose mother received chemotherapy for acute leukaemia during pregnancy, required intensive care because of profound anaemia and neutropenia. Haemopoietic progenitor cell studies showed fetal marrow suppression. Those caring for such mothers and babies should know the possible serious effects chemotherapy for malignancies can have on a developing fetus. Long term follow up of the baby is imperative.